ANALYSIS OF WOMEN WITH BREAST CANCER SUBMITTED TO IMMEDIATE OR DELAYED BREAST RECONSTRUCTION - Ferreira Filho, Darley de Lima; Ferreira, Nancy Cristina Ferraz de Lucena; Ferreira, Thais (Mastology, 2026)
Objective: Breast reconstruction is a right guaranteed by the public health system to patients undergoing mastectomy. However, there are factors that delay the performance of this procedure, mainly in the single health system. This study aims to analyze the characteristics of immediate or delayed reconstructions in women with breast cancer in a referral hospital in the state of Pernambuco (Barao Lucena Hospital). Methods: This is an observational, retrospective, analytical research with a descriptive approach of 400 cases of breast reconstruction from 2010 to 2020. Data were collected through a clinical-surgical questionnaire from patients with breast carcinoma who underwent reconstruction mammary, being later analyzed by the SPSS software version 18 with the percentages of the categories evaluated by the chi-square test, considering the level of significance of 5%. The comparison of analyses was significant (p<0.005), demonstrating that the profile described is the most frequent in the group of patients evaluated. CAAE: 42457420.1.0000.5193. Results: Most patients were with a mean age between 46 and 59 years (45.3%), mixed race (61.1%), married (79.1%), with schooling up to high school (60.7%), housewives (45 %), non-smokers (84.9%), and do not consume alcohol (94.9%). Using the TNM system, 84% of the patients were in the initial stages, underwent immediate reconstruction after mastectomy or sectorectomy (70.3%), and the reconstruction surgeries with regional flaps such as inferior, superior, or mediolateral and implants were performed in 70% of the patients. According to the molecular subtype, luminal A represented 60% of the patients, followed by luminal B with 16%, triple-negative with 15%, and HER2 with 9%. Conclusion: The findings support the fact that patients with high educational levels are able to immediately undergo breast reconstruction. We conclude that the number of immediate breast reconstructions in patients with breast cancer has a significant increase.